Testing Memories of Personally Experienced Events: The Testing Effect Seems Not to Persist in Autobiographical Memory - Emmerdinger, Kathrin J.; Kuhbandner, Christof (Frontiers in Psychology, 2018)
Numerous studies have shown that retrieving contents from memory in a test improves long-term retention for those contents, even when compared to restudying (i.e., the “testing effect”). The beneficial effect of retrieval practice has been demonstrated for many different types of memory representations; however, one particularly important memory system has not been addressed in previous testing effect research: autobiographical memory. The aim of the present study was to examine the effect of retrieving memories for personally experienced events on long-term memory for those events. In an initial elicitation session, participants described memories for personally experienced events in response to a variety of cue words. In a retrieval practice/restudy session the following day, they repeatedly practiced retrieval for half of their memories by recalling and writing down the previously described events; the other half of memories was restudied by rereading and copying the event descriptions. Long-term retention of all previously collected memories was assessed at two different retention intervals (2 weeks and 13 weeks). In the retrieval practice session, a hypermnesic effect emerged, with memory performance increasing across the practice cycles. Long-term memory performance significantly dropped from the 2-weeks to the 13-weeks retention interval, but no significant difference in memory performance was observed between previously repeatedly retrieved and previously repeatedly restudied memories. Thus, in autobiographical memory, retrieval practice seems to be no more beneficial for long-term retention than repeated re-exposure.